PERILAKU KELUARGA DALAM PEMENUHAN ACTIVITY OF DAILY LIVING (ADL) ANGGOTA KELUARGA DENGAN SKIZOFRENIA DI DESA PARINGAN, KECAMATAN JENANGAN, KABUPATEN PONOROGO - Dinda Mar’atush Sholihah; Nurul Sri Wahyuni; Lina Ema Purwanti (Universitas Muhammadiyah Ponorogo, 2017)
Abstract Some symptoms such as losing motivation, responsibilities, apathetic, and social and Activity of Daily Living (ADL, hereafter) disturbance are often experienced by schizophrenia patients. They often experience inhuman treatments such as cruel behavior, isolated or deprived. This study aims to identify family behavior in ADL for schizophrenia’s family.This study is a descriptive study. The populations of the study are all families whose members are schizophrenia in Paringan village, Jenangan sub-district, Ponorogo district.There are 60 respondents taken as the sample of the study. Total sampling is employed to take the sample of the study. Thus, questionnaire is used as the data collection technique. In addition, score T is utilized to analyze the data.The results of the study show that most families, as many as 36 families (60%) have positive behavior and 24 families (40%) have negative behavior for having ADL for those families whose members are schizophrenia. Based on the results on the study, it is expected that the families whose members are schizophrenia should have a better positive behavior for meeting ADL for schizophrenia patients. The results of this study is proposed to the future researchers. The next studies are expected to conduct studies related to Families’ Motivation in Increased Self-Esteem Schizophrenia Patients in the Society. Keywords: Behavior, Family, Activity of Daily Living (ADL), SchizophreniaAbstrak Pasien skizofrenia sering terlihat adanya kemunduran yang ditandai dengan hilangnya motivasi, tanggung jawab, apatis, hubungan sosial dan gangguan pemenuhan ADL. Mereka sering mendapatkan perlakuan yang tidak manusiawi, misalnya kekerasan, diasingkan, diisolasi atau dipasung. Tujuan penelitian ini adalah mengidentifikasi perilaku keluarga dalam pemenuhan ADL anggota keluarga dengan skizofrenia. Desain penelitian yang digunakan adalah deskriptif. Populasi penelitian ini adalah seluruh keluarga di Desa Paringan, Kecamatan Jenangan, Kabupaten Ponorogo yang mempunyai anggota keluarga penderita skizofrenia sejumlah 60 responden. Teknik sampling yang digunakan adalah Total Sampling. Teknik pengumpulan data dengan kuesioner dan teknik analisa menggunakan skor T. Dari hasil penelitian didapatkan sebagian besar yaitu 36 (60%) keluarga berperilaku positif dan hampir setengahnya yaitu 24 (40%) keluargaberperilaku negatif dalam pemenuhan ADL anggota keluarga dengan skizofrenia. Mengacu pada hasil penelitian diharapkan bagi keluarga agar meningkatkan perilaku positifnya dalam pemenuhan ADL pasien sizofrenia . Hasil penelitian ini direkomendasikan untuk peneliti selanjutnya dapat melakukan penelitian tentang Motivasi Keluarga dalam Meningkatan Harga Diri Pasien Skizofrenia di Masyarakat.Kata kunci : Perilaku, Keluarga, Activity of Daily Living(ADL), Skizofren